Achieving foaming control smartly: pre-solubilized flavor oil serves as an in situ homogeneous defoamer. Issue 11 (26th February 2018) - Qi, Na; Sun, Haoyang; Zhao, Hui; Li, Ying
Abstract : The smart foaming control performance of a swollen micelle system and the mechanism at the microscopic level were studied. Abstract : In the wide application of aqueous foam, creating abundant foam and processing appropriate foaming control are both essential, depending upon the actual situation; the latter process is not only harder to achieve, but also more complicated to comprehensively understand on the molecular level. In this paper, a type of natural flavor oil, carvone, was solubilized in a micelle solution of sodium dodecyl sulfate (SDS) to study the effect on the foaming properties. The foamability and foam stability of the swollen micelle solutions were experimentally characterized, and the molecular behavior of the surfactant and oil molecules before, during and after the foaming process were investigated. It was found that the solubilized carvone co-adsorbed with SDS at the gas/water interface and caused a prominent effect on the foam film stability in several approaches, thereby making the flavor oil a possible foam controller that would not inhibit foam formation, but could eliminate foam efficiently once foam was undesired. Interestingly, it was found that the release of flavor in the foaming process was promoted. Detailed discussion of the interfacial behavior of carvone and the effect on the foaming properties of surfactants in different stages of foam may provide a theoretical foundation for exploring green and smart approaches in achieving foaming control.